Penyalahgunaan Karya Sinematografi Yang Disediakan Layanan Over-The-Top Dikaitkan Dengan Prinsip Fair Use - Anzalna Noor Zalika; Rika Ratna Permata; Danrivanto Budhijanto (Widya Yuridika, 2023)
Over-The-Top Services are a concrete form of technological developments whose existence makes it easier for people to carry out daily activities, for example to watch a movie and communicate. The phenomenon related to Over-The-Top Services that recently emerged due to the COVID-19 pandemic is watch party, which is an activity of watching movie together virtually with the help of Over-The-Top Services. This activity has the potential to violate Copyright because it can be categorized as the implementation of the economic rights of the creator or copyright holder of films that are watched without permission. On the other hand, watch party can also be categorized as acts that do not violate Copyright if they meet the fair use requirements based on Law Number 8 of 2014 on Copyright. This research was conducted with the aim of finding answers to these questions. This research was conducted using a normative juridical approach and a qualitative juridical analysis method, in which the author examines in depth the related primary, secondary, and tertiary legal materials. The results of the study indicate that the watch party activity is a form of announcement of creations and includes fair use because it is carried out without commercial purposes.